RETRACTED: The Influence of Compensation, Transactional Leadership Style, Motivation and Work Discipline on Employee Performance in The South Jakarta City Fire and Rescue Department - Oktafian Cahya Dwi Hardin; Herry Krisnandi; Kumba Digdowiseiso (Journal of Social Science)
This research aims to find out and analyze how big it is influence compensation, style leadership transactional, motivation And work discipline on employee performance in the fire and rescue department. The data source in this research is primary data and the type of data used is quantitative data by distributing questionnaires to 100 employees of the fire and rescue department. Deep data testing study This use method analysis descriptive And analysis inferential. The research results show that in partial compensation testing, transactional leadership style, motivation and work discipline influence employee performance. Between compensation (X 1 ), transactional leadership style (X 2 ), motivation (X 3 ) and work discipline (X 4 ) show that they have a positive and significant effect. Based on processing data with use analysis regression multiple linear obtained results equality regression as following Y = 10,108 + 0.368 X 1 + 0.108 X 2 + 0.127 X 3 + 0.124 X 4 . Results study This showing that compensation (X 1 ) have influence positive And significant to performance employee (Y), transactional leadership style (X 2 ) has a positive and significant influence on employee performance (Y), motivation (X 3 ) has a positive and significant influence on employee performance (Y), work discipline (X 4 ) has a positive and significant influence on employee performance (Y). The fire and rescue department needs to evaluate and improve compensation, transactional leadership style, motivation and work discipline already exists to improve employee performance. Keywords: Compensation, Transactional Leadership Style, Motivation, Work Discipline and Employee Performance